Individual distribution and colocalization of nitric oxide synthase with vasoactive intestinal polypeptide and neuropeptide Y in the developing human fetal small intestine - Bagyánszki, Mária (Acta Biologica Szegediensis, 2002)
The appearance, the individual distribution and the pattern of colocalization of nitric oxide synthase (NOS-immunoreactivity, NOSi), vasoactive intestinal peptide (VIP-immunoreactivity, VIPi) and neuropeptide Y (NPY-immunoreactivity, NPYi) immunoreactivity were examined in the developing human fetal small intestine at weeks 12 and 18 of gestation. Neurons expressing VIPi, NPYi and NOSi were observed in the small intestine of the 12-week-old human fetuses and from this age on a gradual increase in the immunoreactivities appeared until week 18 of gestation when a dense network of immunopositive fibres and cell bodies were observed both in the submucous (SmP) and in the myenteric plexuses (MP). The double-labelling immunocytochemistry showed different pattern of the overlapping immunoreactive structures within the myenteric and submucous plexuses. The cellular colocalization of VIPi and NOSi in submucous ganglia were revealed around week 12 of gestation while in the myenteric ganglia cells with overlapping immunoreactivity appeared around week 18. A limited cellular colocalization of NPYi and NOSi were noticed before week 18, and NOSi neurons in the MP of the 12-week-old fetuses were preferentially innervated by NPYi varicosities. These results suggest that VIP, NPY and NO may exert a cooperative action in human fetal gastrointestinal motility.